A Buffering Response in Light of Variation in Core Technology, Perceived Environmental Uncertainty, and Size - Kopp, Daniel; Litschert, Robert J. (Academy of Management Journal, 1980)
The relationships between a particular buffering response (part-time and temporary workers) and variations in core technology, perceived environmental uncertainty, and organization size were examined. A relationship was found between variations in the flexibility of core technology and the amount of buffering, but no significant relationships were found between the buffering response and either perceived environmental uncertainty or organization size.